Adjuvant chemotherapy with paclitaxel and carboplatin in patients with advanced bladder cancer: A study by the hellenic cooperative oncology group - Bamias, A.; Deliveliotis, Ch.; Aravantinos, G.; Kalofonos, Ch.; Karayiannis, A.; Dimopoulos, M.A. (Journal of Urology, 2004)
Purpose: Radical cystectomy represents the treatment of choice for muscle infiltrative bladder carcinoma. Adjuvant chemotherapy has been used to improve outcome after cystectomy. We report results in a prospective cohort of patients at high risk for relapse who were treated with the combination of paclitaxel and carboplatin as adjuvant treatment following cystectomy for muscle invasive bladder cancer. Materials and Methods: A total of 92 patients with extravesical tumor extension (pT 3b or greater) or lymph node involvement (N+) were treated with 4 cycles of paclitaxel at 175 mg/m2 and carboplatin (area under the curve 5 according to the Calvert formula) every 3 weeks following radical cystectomy. Patients were followed every 6 months thereafter. Results: Median followup was 36.6 months. Chemotherapy was well tolerated with 62% of patients receiving 100% of the expected chemotherapy doses without delays. Grade 3 or 4 neutropenia was reported in 19% of patients, while neutropenic fever was reported in 7%. Five-year overall, cause specific and disease-free survival was 28.9% (95% CI 14.8 to 43.0), 36.6% (95% CI 24.4 to 49.7) and 29% (95% CI 16.3 to 42.4), respectively. Conclusions: Adjuvant chemotherapy with paclitaxel and carboplatin is feasible and could be used as adjuvant treatment for high risk bladder carcinoma. Its true value should be assessed in prospective, randomized trials.
Keywords: Bladder; Bladder neoplasms; Carboplatin; Chemotherapy, adjuvant; Paclitaxel